INFLUENCE OF STOCK MARKET LIQUIDITY ON THE GROWTH OF CORPORATE BOND MARKET IN KENYA - Wanyama, Dr. David W. (International Journal of Finance, 2017)
Purpose: The purpose of this study was to analyze how stock market liquidity influence the growth of corporate bond market in Kenya. Methodology: The study used descriptive and causal research designs. Secondary data was used. The sample of the study consisted of daily and monthly time series covering six years beginning January 2009 to December 2014. Unit root tests using Augmented Dickey-Fuller (ADF) and Phillips-Perron tests were done. The study used Eviews econometric software to facilitate empirical analysis of data. Results: Regression of coefficients results shows that stock market liquidity and corporate bonds are positively and significant related (r=8.291, p=0.0008). Unique Contribution to Theory, Practice and Policy: This study recommends study recommends for Policy makers to come up with measures to enhance the liquidity of the stock market which will in turn encourage investment in corporate bonds.